The Influenza Pandemic of 1918–1919 in the British Caribbean - KILLINGRAY, DAVID (Soc Hist Med, 1994)
The influenza pandemic swept through the Caribbean during the period October 1918 to March 1919 and resulted in c. 100 000 deaths. This article focuses on the British possessions and is based principally on official reports and the local press. It looks at how the virus entered and spread through the region, the possible reasons for variations in levels of morbidity and mortality between islands, popular responses to the infection, and the mainly fruitless official attempts to arrest and deal with the disease. Jamaica was the first island to be affected, and along with Belize and Guyana, suffered most severely. A number of islands, particularly those in the eastern Caribbean, appear to have escaped relatively lightly. Although all sections of the population were vulnerable, the heaviest mortality rates were among the very poor, East Indian immigrant labourers, and native Americans. There was also a high toll among males aged 15–40. Altogether the death rate from influenza in the British Caribbean was c. 30 000. In London influenza was added to the official list of British ‘imperial diseases’, and although it was recognized that poverty provided the conditions for the spread of disease, the resources in the Caribbean were barely used to improve standards of living and nutrition.